Attracting Attention: Cheap Managerial Talk and Costly Market Monitoring - ALMAZAN, ANDRES; BANERJI, SANJAY; MOTTA, ADOLFO DE (Journal of Finance, 2008)
ABSTRACT We provide a theory of informal communication—cheap talk—between firms and capital markets that incorporates the role of agency conflicts between managers and shareholders. The analysis suggests that a policy of discretionary disclosure that encourages managers to attract the market's attention when the firm is substantially undervalued can create shareholder value. The theory also relates the credibility of managerial announcements to the use of stock‐based compensation, the presence of informed trading, and the liquidity of the stock. Our results are consistent with the existence of positive announcement effects produced by apparently innocuous corporate events (e.g., stock dividends, name changes).